An Evidence-based Review Of Micro-CT Assessments Of The Postmenopausal Osteoporosis Rat Model - Nadia Mohd Effendy; Nurul Izzah Ibrahim; Norazlina Mohamed; Ahmad Nazrun Shuid (Asian Network for Scientific Information, 2024)
Micro-CT (μCT) is a high resolution imaging tool that is generally used in animal studies. This review evaluates the effectiveness of μCT in assessing bone changes in the postmenopausal osteoporosis rat model. A systematic review of the literature was conducted to identify relevant studies on μCT and postmenopausal osteoporotic bone changes. A comprehensive search via the two databases; Medline via OVID Medline and Scopus was conducted for relevant studies published between 1994 and 2014. The results were limited to research articles published in English, that reported on the association between μCT findings and bone changes in the postmenopausal osteoporosis rat model. Studies were excluded if they were duplicated, did not use an ovariectomized-induced postmenopausal rat model and did not focus on μCT as the primary outcome. The literature search identified 182 potentially relevant articles that were later limited to 22 studies based on the inclusion and exclusion criteria. Fourteen in vitro μCT studies, 7 in vivo μCT studies and one report that combined both in vitro and in vivo μCT studies were included in this review. Of all these studies, 8 studies used μCT alone in assessing bone changes while the remaining studies used μCT analyses together with histomorphometry, DXA and pQCT which enabled a comparison of effectiveness. All the studies reported positive roles of μCT in evaluating bone quality. This evidence-based review highlights the ability of μCT to not only assess bone microarchitecture but also bone mineral density and bone strength.